THE ROLE OF MODERN TECHNOLOGIES AND CLOUD COMPUTING IN ENHANCING THE SECURITY OF ACCOUNTING INFORMATION SYSTEMS - Murtadha Saleh Mahdi; Ahmed Mohammed Ibrahim; Ali Noori Abdulzahra (Scholars Digest Publishing, 2024)
The aim of this research is to provide an overview of the role of modern technologies and cloud computing in enhancing the security of accounting information systems. The researchers employed a descriptive analytical approach and collected primary data through a questionnaire. The questionnaire was distributed to a sample of professionals and academics in the fields of financial accounting and information technology systems who have knowledge and experience in the field of information technology and digital aspects. The data were then analyzed by using SPSS software to test the research hypotheses. The research arrived at several conclusions, where the most important one is that there is a statistically significant effect of cloud computing on the security of accounting information systems. Cloud computing technologies are widely recognized as a valuable tool for enhancing the security of accounting information systems, serving as a strong defense against electronic crimes and accounting fraud, while also preserving the principles of accounting information systems security. To further advance in this field, a series of recommendations were formulated, with particular emphasis on the need for continuous research in cloud computing technology. The importance of accounting information and its effectiveness cannot be overstated, especially in light of the increasing demand for these services. It is essential to explore the interconnection between cloud computing technology and other related domains such as electronic, digital, and internet services and web services. This will help generate greater scientific interest and draw the attention of specialists and accounting authorities to the importance of establishing accounting and auditing standards for accounting information systems services, similar to those applied in advanced countries.
Keywords: Modern Technologies, Accounting Information Systems, Cloud Computing.